Reproductive parameters of the turquoise-fronted parrot (Amazona aestiva) in the dry Chaco forest - Berkunsky, Igor (2017)
The progressive exploitation and destruction of nesting habitat in recent years, combined with the substantial pressure from legal and illegal removal of wild nestlings and adults, justifies the development of a comprehensive study on the reproductive biology of the Turquoise-fronted Parrot (Amazona aestiva). We analyzed breeding parameters in a wild protected population of Turquoise-fronted Parrots in the Chaco forest, Argentina, examining variation among years, over the course of the breeding season, and in relation to the age of the nest. Mean clutch-size per nesting attempt was 3.68 eggs. Hatching success (proportion of eggs laid that hatch) was 0.73. Fledging success (proportion of nestlings that fledge) was 0.88. The overall breeding success (mean number of fledglings per laying female per year) was 0.95. Clutch size did not vary among years but it decreased with the delay of the nest initiation date. Hatching failure was the greatest cause of egg partial losses, and brood reduction was the main cause of nestling partial loses. Brood reduction was positively correlated with clutch size and with egg-laying date. We did not find interannual variation in any of the clutch or brood size variables. Our results showed that the population of Turquoise-fronted Parrots in the dry Chaco forest has high values of clutch size and nestling survival, and low values of hatching success. However, some aspects of the breeding biology need more attention, especially if the species continues to be harvested.